A new species of Metahomaloptera (Teleostei: Balitoridae) from China - Yang, Jian; Chen, Xiaoyong; Yang, Junxing (Zootaxa, 2007)
A new species of Metahomaloptera, M. longicauda, is described from the lower Jinsha River, China. The new species is distinguished from other species of Metahomaloptera by the following combination of characters: pectoral fin with 11– 15 branched rays, tip of pectoral fin extending beyond origin of dorsal fin, pelvic fin with 10–12 branched rays, pelvicfin tip reaching or extending beyond anus, dorsal fin inserting before middle of body, tip of dorsal fin far from vertical line of caudal-fin base, head width 19.4–22.6% SL, pre-pectoral length 8.4–9.9% SL, pre-anal length 69.0–74.3% SL, caudal peduncle length 17.1–20.7% SL, eye diameter 14.6–16.6% HL, caudal peduncle depth 33.7–43.1% caudal peduncle length, mouth width 63.2–75.5% body width at pectoral-fin origin.